Faith or fraud: fortune-telling, spirituality, and the law - Patrick, Jeremy (Law and Society, 2020)
Faith or Fraud? Fortune-Telling, Individual Spirituality, and the Law answers an emerging controversy: Should the law's understanding of religion include the "spiritual but not religious"?.